From Justinian to Branimir - Džino, Danijel, author.
1 online resource (xiv, 258 pages)
Keywords: "From Justinian to Branimir explores the social and political transformation of Dalmatia between c.500 and c.900 AD. The collapse of Dalmatia in the early seventh century is traditionally ascribed to the Slav migrations. However, more recent scholarship has started to challenge this theory, looking instead for alternative explanations for the cultural and social changes that took place during this period. Drawing on both written and material sources, this study utilizes recent archaeological and historical research to provide a new historical narrative of this little-known period in the history of the Balkan peninsula. This book will appeal to scholars and students interested in Byzantine and early medieval Europe, the Balkans and the Mediterranean. It is important reading for both historians and archaeologists"--